Modified treatment for carbonized cellulose nanofiber application in composites. (November 2016) - Ma, Libo; Zhang, Yang; Wang, Siqun
Abstract: In the present study, carbon nanofibers (CNF) from carbonized cellulose nanofibers (CCNF) were prepared by carbonizing freeze-dried cellulose nanofibers first, then preparing acrylonitrile-butadienestyrene (ABS)/CCNF nanocomposites by extruder. To increase the dispersibility and operability of the CCNF, the ultrasound-assisted master batch method was adopted to make an ABS/CCNF master batch. Dicumyl peroxide and maleic anhydride were added to increase the interface compatibility between the CCNF and the ABS by reactive extrusion. The surface morphology, chemical structure, and mechanical properties of the ABS/CCNF nanocomposites were characterized by SEM, FTIR, and DMA/tensile tests, respectively. The tensile strength of ABS/CCNF was improved 36% compared to that of ABS. The improved properties demonstrated that the approach used in this study has the potential to solve the bottleneck issues of mass producing and applying CNF in a green way.